2011
DOI: 10.1177/0309364610397087
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of life in lower limb amputees

Abstract: Background: Quality of life (QoL) is increasingly being recognized as an important outcome for rehabilitation programs, and has mainly been used to compare the efficacy of interventions or to compare amputees with other diseased populations. There is relatively a limited number of studies primarily focusing on analyzing the multitude of factors influencing QoL in amputees. Objectives: To identify important background and amputation related factors which affect quality of life (QoL) in lower limb amputees, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
231
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(272 citation statements)
references
References 43 publications
16
231
3
3
Order By: Relevance
“…As a result, evaluation of individual participation is traditionally accomplished using global surveys or self-report instruments [2,[28][29][30]. These subjective tools have suggested that restrictions are common among persons with lower-limb loss [31][32][33][34][35][36]. However, differences between self-report and assessed mobility outcomes in this population [25] suggest that surveys alone may be insufficient to fully characterize restrictions experienced by persons with TFA.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, evaluation of individual participation is traditionally accomplished using global surveys or self-report instruments [2,[28][29][30]. These subjective tools have suggested that restrictions are common among persons with lower-limb loss [31][32][33][34][35][36]. However, differences between self-report and assessed mobility outcomes in this population [25] suggest that surveys alone may be insufficient to fully characterize restrictions experienced by persons with TFA.…”
Section: Introductionmentioning
confidence: 99%
“…However, psychological issues, such as how an amputee feels about his or her amputation and prostheses, are also important factors. Previous reports have suggested that in order to provide a complete assessment of the benefits of an intervention, evidence of its effect on health-related quality of life (QOL) must be reported [6][7][8]. People with recent lower-limb amputations will continue to adapt to using a prosthetic limb during ADLs as they rejoin the work place and participate in recreational activities including sport and exercise [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Reports of QOL have varied, with people with lowerlimb amputation being equal to or higher [11][12] and lower [8][9][10][13][14] than normative reference data, indicating that no general consensus exists on how amputation affects QOL. However, a higher level of amputation (e.g., transfemoral vs transtibial) has been associated with decreased QOL [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations